(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The false armyworm insect Lucania loreyi was laboratory breeding and feeding at nutrient medium containing a groats of corn in an incubator with temperature of 27 ± 2 and relative humidity of 65 ± 5% in order to determine the life cycle and seven successive generations of the insect was breed began from September to the end of August 2016, where the total hatchling stage reached 3-13 days At a temperature ranging from 20-27 m, the larvae ranged from 13-57 days and the pupae persisted from 7-33 days At a temperature ranging from 20-27 m while the longevity of adults ranged from 1-34 days and the full life cycle was about 33-109 days. The current study is the first in Iraq to study the insect life on the corn crop.